A Sharpe ratio-integrated indicator system for land use changes ecological risks: Within coupled disaster-economic assessment frameworks - Xuyang Zhang; Wei Song; He Gao (Ecological Indicators)
Global climate change and human-induced land-use changes have threatened the stability of ecosystem service provision and intensified ecological risks. However, the ecological risk of land-use change (ERLUC) remains an emerging concept with unclear definitions and assessment methodologies. This study proposes a novel Sharpe ratiobased Ecological Risk Index (ERI) that integrates the probability of land use change occurrence with expected ecological benefits, applied to the North China Plain (NCP). Key findings include: (1) Probability of land-use change can be defined as the likelihood of future transitions, while expected ecological benefits represent potential ecosystem service gains or losses from such changes. The Sharpe ratio effectively couples these parameters for risk assessment. (2) Under three scenarios – natural development, urban expansion, and ecological conservation – the mean ERI values were 0.4718, 0.4719, and 0.4703 respectively, indicating highest overall risk in urban expansion. (3) Spatial analysis revealed similar risk gradation patterns across the plain, dominated by medium–high risk areas (20.33%), followed by medium-risk (30.21%), with relatively smaller proportions of high-risk (13.77%) and medium–low risk (14.23%) zones. (4) Future projections show escalating risks in eastern regions, particularly along urban peripheries. This framework advances ecological risk science by integrating financial risk theory into land system analysis, providing policymakers with spatial targeting tools to balance developmental priorities and ecosystem security in rapidly urbanizing regions.